Monomethylsulochrin isolated from biomass extract of Aspergillus sp. against Leishmania amazonensis: In vitro biological evaluation and molecular docking - Silva-Silva, João Victor; Moreira, Rosiane Fernandes; Watanabe, Luciano Almeida; de Souza, Celeste da Silva Freitas; Hardoim, Daiana de Jesus; Taniwaki, Noemi Nosomi; Bertho, Alvaro Luiz; Teixeira, Kerolain Faoro; Cenci, Arthur Ribeiro; Doring, Thiago Henrique; Júnior, José Wilmo da Cruz; de Oliveira, Aldo Sena; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Leishmaniasis represents a serious world health problem, with 1 billion people being exposed to infection and a broad spectrum of clinical manifestations with a potentially fatal outcome. Based on the limitations observed in the treatment of leishmaniasis, such as high cost, significant adverse effects, and the potential for drug resistance, the aim of the present study was to evaluate the leishmanicidal activity of the compounds pseurotin A and monomethylsulochrin isolated from the biomass extract of Aspergillus sp. The chromatographic profiles of the extract were determined by high-performance liquid chromatography coupled with a diode-array UV-Vis detector (HPLC-DAD-UV), and the molecular identification of the pseurotin A and monomethylsulochrin were carried out by electrospray ionization mass spectrometry in tandem (LC-ESI-MS-MS) and nuclear magnetic resonance (NMR). Antileishmanial activity was assayed against promastigote and intracellular amastigote of Leishmania amazonensis. As a control, cytotoxicity assays were performed in non-infected BALB/c peritoneal macrophages. Ultrastructural alterations in parasites were evaluated by transmission electron microscopy. Changes in mitochondrial membrane potential were determined by flow cytometry. Only monomethylsulochrin inhibited the promastigote growth (IC50 18.04 ± 1.11 µM), with cytotoxicity to peritoneal macrophages (CC50 5.09 91.63 ± 1.28 µM). Activity against intracellular amastigote forms (IC50 5.09 ± 1.06 µM) revealed an increase in antileishmanial activity when compared with promastigotes. In addition to a statistically significant reduction in the evaluated infection parameters, monomethylsulochrin altered the ultrastructure of the promastigote forms with atypical vacuoles, electron-dense corpuscles in the cytoplasm, changes at the mitochondria outer membrane and abnormal disposition around the kinetoplast. It was showed that monomethylsulochrin leads to a decrease in the mitochondrial membrane potential (25.9%, p = 0.0286). Molecular modeling studies revealed that monomethylsulochrin can act as inhibitor of sterol 14-alpha-demethylase (CYP51), a therapeutic target for human trypanosomiasis and leishmaniasis. Assessed for its drug likeness, monomethylsulochrin follows the Lipinski Rule of five and Ghose, Veber, Egan, and Muegge criteria. Furthermore, monomethylsulochrin can be used as a reference in the development of novel and therapeutically useful antileishmanial agents.